Strategic Industry in Islamic Political Economy Perspective - Alamsyah, Indra Fajar; Uddin, Md. Nazim (Perhimpunan Intelektual Muslim Indonesia, 2024)
The development of strategic industries in Muslim countries in general, and specifically Indonesia, has found stagnant conditions, not developed and not even made a top priority in the concept of state development they are designing. This is in contrast to capitalist countries which are competing to become a new face as a country with the forefront strategic industry. The purpose of this article is to provide a conceptual description of thinking of Muslim countries in viewing sovereignty. Sovereignty in these days means independence from various dependencies, especially political-economic dependence. This study used a qualitative library research method. the results of the study found gaps in the concept of development in Muslim countries in the concept of development towards sovereignty through strategic industries. The novelty of this concept is to see the potential of ASEAN countries, especially Indonesia, to be able to take a big role in an important strategic industrial position for Muslim countries.